Peran Tata Kelola Perusahaan dalam Memoderasi Dampak Kebijakan Investasi, Dividen, dan Profitabilitas pada Kinerja Laba Bank di BEI (2021–2023) - Elsa Afrelia; Naomi Kezia; Sabrina Fricilya Juwita Tampubolon; Viola Caroline Br. Samosir; Sulia Sulia (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the role of corporate governance in moderating the effect of investment policy, dividend policy, and profitability on the earnings performance of banks listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Earnings performance is measured using Return on Assets (ROA), while the independent variables include capital expenditure to total assets ratio (CapEx/TA), dividend payout ratio (DPR), and return on equity (ROE). Corporate governance is measured using the Corporate Governance Index (CGI). The research adopts a quantitative approach with a causal-comparative design. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that investment policy and profitability have a significant positive effect on earnings performance, while dividend policy does not have a significant effect. Furthermore, corporate governance is proven to significantly strengthen the impact of investment policy and profitability on earnings performance. However, no moderating effect of corporate governance is found in the relationship between dividend policy and earnings performance. The R² value of 0.64 indicates that the model has strong predictive power for earnings performance. This study highlights the importance of effective corporate governance in reinforcing managerial decisions, particularly in the areas of investment and profitability, to enhance the financial efficiency of banks in Indonesia. The findings offer practical contributions for bank management and policy implications for regulators in strengthening the corporate governance structure in the banking sector.